Ethnicity and Conflict in a Post-Communist World
XX, 276 p.
Keywords: The post-Communist world has seen a dramatic revival of ethnicity and nationalism. The volume explores the contemporary sources, scope and intensity of nationality conflicts in the context of a disintegrating Soviet Empire. The authors address themselves to the resurgence of ethnicity and nationalism within the former Soviet imperium, Yugoslavia, Hungary, Bulgaria and China and examine the consequences of perestroika and glasnost. Central issues involve identity formation, the nature and implications of ethnic and internal conflicts and possible paths toward resolution.